2019
DOI: 10.1186/s40816-018-0096-5
|View full text |Cite
|
Sign up to set email alerts
|

Solanum nigrum confers protection against CCl4-induced experimental hepatotoxicity by increasing hepatic protein synthesis and regulation of energy metabolism

Abstract: Background: Hepatotoxicity induced by carbon tetrachloride (CCl 4) is used as an experimental model to screen phytochemicals with liver protecting activity. Solanum nigrum (SN) is a shrub which is widely distributed throughout India. Traditionally the plant has been used for curing various ailments related to gastroenterology and hepatology. The present study was performed to evaluate the hepatoprotective property of S. nigrum extract standardized for its flavonoid content against CCl 4-induced hepatotoxicity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…Finally, the presence of three herbal components also produced a possible synergistic effect in ameliorating CCl 4 induced hepatic injury that needs to be explored further. The dose of individual plant extract applied at the highest tested dose of SKK (200 mg/kg) was relatively low as compared to several other published studies using individual plant extracts of B. diffusa L. , P. niruri L., and S. nigrum L. for hepatoprotection in CCl 4 stimulated murine models (Chandan et al, 1991;Manjrekar et al, 2008;Beedimani and Jeevangi, 2017;Krithika and Verma, 2019).…”
Section: Discussionmentioning
confidence: 86%
“…Finally, the presence of three herbal components also produced a possible synergistic effect in ameliorating CCl 4 induced hepatic injury that needs to be explored further. The dose of individual plant extract applied at the highest tested dose of SKK (200 mg/kg) was relatively low as compared to several other published studies using individual plant extracts of B. diffusa L. , P. niruri L., and S. nigrum L. for hepatoprotection in CCl 4 stimulated murine models (Chandan et al, 1991;Manjrekar et al, 2008;Beedimani and Jeevangi, 2017;Krithika and Verma, 2019).…”
Section: Discussionmentioning
confidence: 86%
“…CCl 4 is a well-known hepatotoxin that results in marked degeneration of centrilobular fat and liver damage induced by extensively utilized as an experimental model for the evaluation of potent hepatoprotective agents (39). The ndings revealed that the levels of liver serum transaminases i.e.…”
Section: Discussionmentioning
confidence: 99%
“…From the literature, in vitro and in vivo models have been exploited to investigate the protective role of some crude extracts or isolated compounds against the toxic effect of some toxins on the liver cells [ 96 , 97 ]. For example, the protection against liver damage induced by carbon tetrachloride (CCl 4 ) has been extensively studied [ 98 ]. The study carried out by Molehin et al [ 16 ] reported the hepatoprotective role of methanolic extract of C. volubile leaves against oxidative stress and liver toxicity induced by CCl 4 in rats.…”
Section: Pharmacological Potentials Of C Volubilementioning
confidence: 99%